Revitalizing preschool minds: a fresh approach to arts-based brain health interventions - Siette, Joyce; Anderson, Emily; Catanzaro, Michelle (Frontiers in Public Health, 2024)
IntroductionBrain health interventions seek to cultivate enduring, health-promoting behaviors for an enhanced quality of life. Despite this objective, achieving sustained adoption and engagement of healthy lifestyle behaviors remains a challenge, prompting the exploration of innovative avenues for promoting brain health. The potential of integrating brain health education in younger populations is particularly promising, given the likelihood of these habits persisting into adulthood. This study thus aimed to identify parental perspectives on a performing arts-based brain health intervention for implementation in preschool settings.MethodsPreschool parents and early learning center staff participated in three focus co-design groups (n = 12) to create a prototypical performing arts brain health intervention. Each focus group was recorded, transcribed and analyzed using deductive thematic analysis.ResultsThree main themes for effective brain health interventions in preschool settings were identified: optimizing logistical processes to ensure efficient delivery and scalability, recognizing motivation as a central factor influencing sustained engagement across all stakeholders, and tailoring educational content with specialized explanations for children to enhance comprehension and relatability. A new implementation approach was proposed to support an arts-based brain health intervention designed for preschools.ConclusionsThese findings have important implications for the future of brain health education focusing on youth populations and a lifelong approach to dementia risk prevention strategies. By addressing logistical challenges, prioritizing motivation, and tailoring explanations to the unique needs of children, future programs can be more adaptable and successful in fostering positive and sustainable brain health behaviors.